Duress Prevention in Juvenile Criminal Proceedings: Comparative Analysis of The United Kingdom and Indonesia - Tantimin; Situmeang, Ampuan; Febriyani, Emiliya (LITIGASI, 2025)
The juvenile justice system is intrinsically related to youth development, as it is responsible for the education and rehabilitation of children who have committed or are suspected of committing a crime. Juvenile crimes must go through criminal proceedings before being tried in court. However, discussions on preventing duress during these proceedings in Indonesia remain limited. This research aims to analyze efforts to prevent duress during juvenile criminal proceedings in Indonesia, highlighting potential gaps and comparing them to the United Kingdom's juvenile justice system. Utilizing the normative research method with the support of the comparative approach, this study examines existing Indonesian laws and their implementation while juxtaposing them with the UK’s juvenile justice framework. The analysis reveals significant opportunities for duress to occur within Indonesia’s juvenile justice system, contrasting with the UK’s system, which has a more structured set of legal norms. Based on these findings, this research proposes a model for legal development, focusing on closing procedural gaps that allow duress to occur during juvenile criminal proceedings in Indonesia.